Thermal Environment and Aeroheating Mechanism of Protuberances on Mars Entry Capsule - Miao Wenbo (American Association for the Advancement of Science (AAAS), 2021)
Mars has only thin atmosphere composed mainly of carbon dioxide that differs significantly from the atmosphere of Earth in terms of characteristics of reentry flows. To connect with the orbiter, the Mars entry capsule is provided with titanium pipes and other units installed on the heat-shield. These units will create significant local interaction flow on the surface of the capsule and cause additional heating on the surface of the shield during the entry of the capsule. With a view to interaction thermal environment issues for the surface of the shield, in this paper, the characteristics of protrusion interaction flow on different location of the shield were studied by means of numerical simulation. Heating mechanisms of protuberances on different location were derived by analyzing characteristic parameters such as local flow velocity, pressure, and Mach number. The results show that the interaction thermal environment of protuberances in the windward area is smaller than that of protuberances in the leeward area, mainly because subsonic flow dominates in the windward area, and the interaction is weak, while in the leeward area, the direction of flow intersects with protuberances to form a boundary layer shear flow, which results in a stronger interaction before the protuberances.